Postcovid pulmonary complication - Tomasz Korzec; Przemysław Raczkiewicz; Maria Kalicka; Konrad Kania; Katarzyna Cyboran (Kazimierz Wielki University, 2021)
Introduction:   The World Health Organization in March 2020 announced a pandemic of COVID-19 disease caused by the SARS-CoV-2 virus. It is one of the seven species known to be pathogenic to humans in this group of viruses. The incubation period of the virus is 2-14 days, usually about 5 days.  SARS-CoV-2 uses the ACE2 receptor to enter the host's mucosa and cause an active infection. Symptomatic infection may be complicated by reversible or irreversible changes in the lungs and pulmonary embolism.   Method:   Recent literature was reviewed based on PubMEd, Google scholar, using   words: covid lung, post covid lung, post covid, covid lung fibrosis,   Objective: Systematisation of information on pulmonary postovid complications